Use of Real-Time PCR To Detect and Quantify Mycoplasma haemofelis and “Candidatus Mycoplasma haemominutum” DNA - Tasker, Séverine (American Society for Microbiology, 2003)
A real-time PCR assay using Taqman probes was developed to detect and quantify Mycoplasma haemofelis and “Candidatus Mycoplasma haemominutum” in feline blood samples. The assay was rapid and sensitive and was successfully used to monitor the in vivo kinetics of cats experimentally infected with each species.